EFECTO DE TRES DOSIS DE ESTIÉRCOL DE OVINO EN EL RENDIMIENTO DE Spinacea oleracea L. VAR. VIROFLAY EN SANTIAGO DE CHUCO, LA LIBERTAD - Castillo Velasquez, Wilder Orlando (2018)
The performance of three doses of sheep manure on the yield of Spinacea oleracea L. Var. Viroflay, the statistical design of randomized complete blocks with four repetitions was used. Each experimental unit consisted of a plot of 2m x 2.25m with a density of 90 plants, direct sowing per blows at a distance of 20 cm x 25cm. The analysis of the results was carried out through an analysis of variance. The plants developed in temperatures that ranged between 6 ° C and 22 ° C. The yield was highly significant among the treatments, the highest yield was obtained in T3 (54118.19kg / ha-1) being higher than T2 (46265.47kg / ha-1), T1 (40236.37 kg / ha-1) and T0 (18332.83kg / ha-1). T3 presented the highest plant (32.443 cm), the largest number of leaves (30.88) and leaf area per plant (3649.06 cm2). The three doses showed different yields at T0 (18332.83kg / ha-1).